Study on Information-Seeking Behavior of Social Sciences: Exploring the Challenges and Practices of Information Seeking Behavior in Social Sciences (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Information seeking behavior refers to the way people search and utilize information. Thisstudy focuses on information-seeking behavior of social sciences. The inflation of the scientificpublication puts a hard pressure on the academics in this respect, they developed new digital practices tocope with this situation. With the uprising of information Communication Technologies (ICTs) flow ofinformation is rapidly enhanced. User needs are fulfilled through a single click. Wide-ranging reading ofvolume of information is an additional dilemma. It is a reality that wide range information createambiguous in taking final decision. In this circumstance inspired information seeking is exceedinglytricky. and the mainly study in which discussed about Information Seeking, Information SeekingBehavior, Information Communication Technologies (ICTs) in the legal profession, Information SeekingBehavior in Digital Environment, Purpose of Seeking Information, Type of Information often search bysocial scientists, Time Spent in various purposes by social scientists